STABILITAS PEMERINTAHAN DALAM PERSPEKTIF ALQURAN - Mairizal, T Mairizal (Jurnal At-Tibyan: Jurnal Ilmu Alquran dan Tafsir, 2018)
Discourse on the concept of government is always being a lactual issue in Indonesia, especially in the lead up to regional elections or presidential elections. But essentially legislative elections cannot be ignored, each contestant in the general election competes to attract the votes of the people without regard to their spiritual competence. In this case, Alquran has formulated the basic concept of the government system. And this article tries to describe these basic concepts by using thematic and semantic approaches. By tracing various relevant terms, at least the Alquran uses awliya, khalifah, and ulil amri terms. These terms show leadership includes the executive and legislature. To be a leader in a government, at least professional competence and physical abilities are needed. The stability of a government depends absolutely on the ability of the leader to carry out his obligations. Although religious status is still disputed, but as long as it is not related to the divine aspect, the people must obey the leader even though many things are not liked by him